More than Pictures: When MS Imaging Meets Histology. (August 2016) - Dong, Yonghui; Li, Bin; Aharoni, Asaph
Abstract : Attaining high-resolution spatial information is a recurrent challenge in biological research, particularly in the case of small-molecule distribution. Mass spectrometry imaging (MSI) is an innovative molecular histology technique that could provide such information. It allows in situ and label-free measurement of both the abundance and distribution of a variety of molecules at the tissue or single cell level. The application of MSI in plant research has received considerable attention; thus, in this review, we describe the current state of MSI in plants. In particular, we present an overview of MSI approaches, highlight the recent technical and methodological developments, and discuss a range of applications contributing to the field of plant science. Trends: Understanding the chemical complexity of plants requires novel technologies to track metabolites at the highest spatial resolution. MSI is emerging as an advanced and essential molecular histology approach to map the distribution of plant molecules. Recent technical and methodological advances in MSI technology have permitted its application in various fields of plant research.